Philippine lichens with bulbate cilia - bulbothrix and relicina (Parmeliaceae) - Bawingan, Paulina; Lardizaval, Mechell; Elix, John (2019)
This paper presents a taxonomic treatment of Bulbothrix and Relicina lichens (Ascomycota, Parmeliaceae) collected in the Philippines, two genera characterized by the presence of bulbate cilia. A total of five species of Bulbothrix and fifteen species of Relicina were identified, with one new record for each genus. The Philippines is a major center of diversity for Relicina. (Author's abstract)